Preoperative Factors Associated with Improvement in Visual Acuity after Globe Rupture Treatment. Issue 5 (September 2013) - Nishide, Tadayuki; Hayakawa, Natsuki; Nakanishi, Misako; Ishii, Mai; Kimura, Ikuko; Shibuya, Etsuko; Nomura, Eiichi; Mizuki, Nobuhisa
Purpose: Globe rupture is a serious condition. Despite advancements in vitrectomy, the postoperative prognosis for visual acuity remains poor in many cases. We conducted multiple regression analysis to identify preoperative factors associated with postoperative visual acuity . Methods: Subjects comprised 24 patients with globe rupture in one eye who had 5 consecutive years of consultation and were followed up for 12 months or longer. Subjects comprised 13 males and 11 females with a mean age of 67.8 ± 17.4 years. Our methods involved performing multiple regression analysis with age, preoperative visual acuity, scope of injury, number of surgeries, hyphema, vitreous hemorrhage, retinal detachment, and subchoroidal hemorrhage as explanatory variables, and postoperative visual acuity as the response variable . Results: Preoperative visual acuity and scope of retinal detachment were explanatory factors found to correlate significantly with postoperative visual acuity after globe rupture . Conclusions: Our results demonstrate that postoperative visual acuity can be predicted to some degree by preoperative visual acuity and the scope of retinal detachment .